1966
DOI: 10.1088/0029-5515/6/3/011
|View full text |Cite
|
Sign up to set email alerts
|

Critical voltage of a rotating plasma

Abstract: The accessible voltage levels have been determined for a rotating plasma device in which the confinement region surrounds a ring-shaped coil that is suspended by a single rod. (i) There exists a sharply defined critical voltage and a corresponding velocity limit which cannot be exceeded by a moderately large power input. This is clearly shown with the present apparatus where the plasma voltage slowly approaches the critical level from below and where the insulator consists only of a narrow rod. (ii) The critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…This limit can only be exceeded once the plasma is almost entirely ionized meaning total ionization is associated with a sharp rise in plasma velocity. Many other similar laboratory experiments subsequently verified the presence of a critical velocity in several different kinds of discharges (Angerth et al, 19 Lehnert et al; 20 or reviews by Danielsson 21 and Sherman, 22 for example) and also in industrial discharges, such as thin film deposition magnetron plasmas. 23 There is also a number of results from astrophysical observations that show the existence of a critical velocity ionization process.…”
Section: Introductionmentioning
confidence: 88%
“…This limit can only be exceeded once the plasma is almost entirely ionized meaning total ionization is associated with a sharp rise in plasma velocity. Many other similar laboratory experiments subsequently verified the presence of a critical velocity in several different kinds of discharges (Angerth et al, 19 Lehnert et al; 20 or reviews by Danielsson 21 and Sherman, 22 for example) and also in industrial discharges, such as thin film deposition magnetron plasmas. 23 There is also a number of results from astrophysical observations that show the existence of a critical velocity ionization process.…”
Section: Introductionmentioning
confidence: 88%
“…7,12 Because of the electrodes, there must be sufficient conductivity along the field lines to carry power and maintain the rotation. If instead the rotation is produced by waves, the plasma density could be reduced where the field line intersects the containment vessel.…”
Section: Transferring Energy To the Fieldmentioning
confidence: 99%
“…In 1954, Alfv6n postulated that rapid ionization of a neutral gas occurs when it moves through a magnetized plasma with a velocity whose component perpendicular to the magnetic field exceeds a critical value v c. Alfv6n [1954] suggested that v c is given by equating the kinetic energy of the neutral atoms to their ionization energy •bi, i.e., Vc = (2cki/m) •/2. Since then the critical ionization velocity (CIV) phenomenon has been confirmed by laboratory experiments (e.g., by Fahleson [1961], Lehnert et al [1966], Himreel et al [1976], and Mb'bius et al [1979]) and by neutral gas release experiments in the auroral ionosphere [Haerendel, 1982]. It has been discussed in connection with the shuttle glow [Papadopoulos, 1984] and as a means of providing rapid ionization in various astrophysical situations [Galeev, 1981;Formisano et al, 1982].…”
Section: Introductionmentioning
confidence: 97%